Genomic DNA damage induced by co-exposure to DNA damaging agents and pulsed magnetic field - López-Díaz, Beatriz; Mercado-Sáenz, Silvia; Burgos-Molina, Antonio Manuel; González Vidal, Alejandro; Sendra-Portero, Francisco; Ruiz-Gómez, Miguel José (Taylor & Francis, 2023)
Purpose: Many articles describe the effects of extremely low-frequency magnetic fields (MFs) on DNA damage induction. However, the mechanism of MF interaction with living matter is not yet known with certainty. Some works suggest that MF could induce an increase in the efficacy of reactive oxygen species (ROS) production. This work investigates whether pulsed MF exposure produces alterations in genomic DNA damage induced by co-exposure to DNA damaging agents (bleomycin and methyl methanesulfonate (MMS)). Materials and methods: Genomic DNA, prepared from S. cerevisiae cultures, was exposed to pulsed MF (1.5 mT peak, 25 Hz) and MMS (0–1%) (15–60 min), and to MF and bleomycin (0–0.6 IU/mL) (24–72 h). The damage induced to DNA was evaluated by electrophoresis and image analysis. Results: Pulsed MF induced an increment in the level of DNA damage produced by MMS and bleomycin in all groups at the exposure conditions assayed. Conclusions: Pulsed MF could modulate the cytotoxic action of MMS and bleomycin. The observed effect could be the result of a multifactorial process influenced by the type of agent that damages DNA, the dose, and the duration of the exposure to the pulsed MF.
https://openpolicyfinder.jisc.ac.uk/id/publication/911
Keywords: Acido desoxirribonucleico - Alteración; Carcinógenos; Campos electromagnéticos - Aspectos sanitarios; Yeast; DNA damage; Methyl methanesulfonate; Bleomycin; Pulsed magnetic field